Population pharmacokinetics of oral levofloxacin in healthy volunteers and dosing optimization for multidrug‐resistant tuberculosis therapy. (19th June 2021) - Boonpeng, Apinya; Jaruratanasirikul, Sutep; Wattanavijitkul, Thitima; Nawakitrangsan, Monchana; Samaeng, Maseetoh
Abstract: Levofloxacin is considered a key component of a multidrug‐resistant tuberculosis (MDR‐TB) regimen. However, there is considerable concern regarding the subtherapeutic concentrations of the currently used doses and the development of drug resistance. Therefore, this study aimed to describe the population pharmacokinetics (PPK) of oral levofloxacin in healthy volunteers and to evaluate the probability of target attainment (PTA) in an attempt to optimize the dosing regimens for MDR‐TB therapy. Data of levofloxacin in healthy volunteers from a previous study were used to construct a PPK model. Monte Carlo simulations were performed to derive the PTAs of various regimens. A two‐compartment model with linear elimination and transit absorption compartments best described the pharmacokinetics (PK) of levofloxacin. The estimated PK parameters (interindividual variability, %) were: apparent clearance 8.32 L h −1 (22.6%), apparent central volume of distribution 35.8 L (45.2%), apparent peripheral volume of distribution 39.7 L, intercompartmental clearance 40.6 L h −1 (43.8%), absorption rate constant 7.45 h −1 (150%), mean absorption transit time 0.355 h (52.4%), and total number of transit compartments 6.01 (131.9%). Monte Carlo simulations using levofloxacin 750–1000 mg yielded a probability of achieving a target free area under the concentration–time curve/minimum inhibitory concentration (MIC) of 100 at greater than 90% for Mycobacterium tuberculosis with an MIC < 0.5 mg L −1, while a dose of 1500 mg was required for strains with an MIC of 1 mg L −1 . A higher dose of levofloxacin might be needed to treat tuberculosis. However, further studies on the efficacy and safety of this dose are needed to confirm our findings. Abstract : Our simulations showed that the currently recommended dose of levofloxacin might be suboptimal for the treatment of tuberculosis; using a higher dose (≥1500 mg) could be needed to improve its efficacy.